Paraguay : Request for a Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
The Paraguayan authorities have prepared an economic program to stabilize their macroeconomic situation and begin a process of structural reform. Fiscal adjustment and structural reforms should pave the way for more rapid growth over the medium term. Despite these expected improvements in economic policies and performance, Paraguay remains vulnerable to external shocks. The fiscal situation has deteriorated sharply in recent years. Severe financing constraints have produced sizable public sector payments arrears. On the revenue side, the government's fiscal strategy is to raise revenues while minimizing increases in tax rates.